Hypofractionated Radiotherapy in Oesophageal Cancer for Patients Unfit for Systemic Therapy: A Retrospective Single-Centre Analysis. Issue 6 (June 2019) - Jones, C.M.; Spencer, K.; Hitchen, C.; Pelly, T.; Wood, B.; Hatfield, P.; Crellin, A.; Sebag-Montefiore, D.; Goody, R.; Crosby, T.; Radhakrishna, G.
Abstract: Aims: Chemoradiotherapy (CRT) is established as a superior treatment option to definitive radiotherapy in the non-surgical management of oesophageal cancer. For patients precluded from CRT through choice or comorbidity there is little evidence to guide delivery of single-modality radiotherapy. In this study we outline outcomes for patients unfit for CRT who received a hypofractionated radiotherapy (HRT) regimen. Materials and methods: A retrospective UK single-centre analysis of 61 consecutive patients with lower- or middle-third adenocarcinoma (OAC; 61%) or squamous cell carcinoma of the oesophagus managed using HRT with radical intent between April 2009 and 2014. Treatment consisted of 50 Gy in 16 fractions ( n  = 49, 80.3%) or 50–52.5 Gy in 20 fractions ( n  = 12, 19.7%). Outcomes were referenced against a contemporaneous comparator cohort of 80 (54% OAC) consecutive patients managed with conventionally fractionated CRT within the same centre. Results: Three-year and median overall survival were, respectively, 56.9% and 29 months with HRT compared with 55.5% and 26 months for CRT; adjusted hazard ratio 0.79 (95% confidence interval 0.48–1.28). Grade 3 and 4 toxicity rates were low at 16.4% ( n  = 10) for those receiving HRT and 40.2% ( n  = 32) for the CRT group. In patients with OAC, CRT delivered superior overall survival (hazard ratio 0.46; 95% confidence interval 0.25–0.85) and progression-free survival (hazard ratio 0.45; 95% confidence interval 0.23–0.88) when compared with HRT. Conclusions: The HRT regimen described here was safe and tolerable in patients unable to receive CRT, and delivered promising survival outcomes. The use of HRT for the treatment of oesophageal cancer, both alone and as a sequential or concurrent treatment with chemotherapy, requires further study. New precision radiotherapy technologies may provide additional scope for improving outcomes in oesophageal cancer using HRT-based approaches and should be evaluated. Highlights: In oesophageal cancer, hypofractionated radiotherapy is safe and tolerable. Outcomes following hypofractionated radiotherapy are very encouraging. Response to treatment in oesophageal cancer dependent on tissue subtype. Potential to combine this approach and precision radiotherapy approaches. Findings relevant to the use of proton-beam therapy.